Cohort Profile: TwinsUK and Healthy Ageing Twin Study - Moayyeri, Alireza (Oxford University Press, 2013)
The UK's largest registry of adult twins, or TwinsUK Registry, started in 1992 and encompasses about 12 000 volunteer twins from all over the United Kingdom. More than 70% of the registered twins have filled at least one detailed health questionnaire and about half of them undergone a baseline comprehensive assessment and two follow-up clinical evaluations. The most recent follow-up visit, known as Healthy Ageing Twin Study (HATS), involved 3125 female twins aged >40 years with at least one previous clinical assessment to enable inspection of longitudinal changes in ageing traits and their genetic and environmental components. The study benefits from several state-of-the-art OMICs studies including genome-wide association, next-generation genome and transcriptome sequencing, and epigenetic and metabolomic profiles. This makes our cohort as one of the most deeply phenotyped and genotyped in the world. Several collaborative projects in the field of epidemiology of complex disorders are ongoing in our cohort and interested researchers are encouraged to get in contact for future collaborations.